Simultaneous Determination of 39 Plant Toxins in Honey by Ultra-high Performance Liquid Chromatography-Tandem Mass Spectrometry with Solid Phase Extraction - LIU Chuan, CHEN Yanqiu, LIN Hao, WANG Luyao, SHI Peiyu, LIU Rong, WANG Yi, WU Wenlin, MAO Rui, XIAO Quanwei, SONG Juan, DAI Qin (Shipin Kexue)
To effectively assess food safety risks associated with potential plant toxin residues present in honey, this study aimed to establish and validate a method for the detection of 39 plant toxins in honey using solid-phase extraction combined with ultra-high performance liquid chromatography-tandem mass spectrometry (SPE-UPLC-MS/MS). The developed method involved sample extraction with 0.1% formic acid, purification using a hydrophilic-lipophilic balanced (HLB) cartridge, detection in the multiple reaction monitoring (MRM) mode, and quantification using the matrix-matched external standard method. The calibration curves exhibited good linearity for all the analytes. Average recoveries ranged from 78.7% to 112.8% with relative standard deviation (RSD) between 1.6% and 15.2% (n = 6). This method was characterized by ease of operation, high throughput and high sensitivity, and could be used for the monitoring these toxins in honey. Varying levels of pyrrolizidine alkaloids (PAs) and rhodojaponin III were detected in some of the 36 tested batches of honey, confirming the presence of phytotoxin residue risks in honey.